Penerapan Metode Preference Rangking Organization Method For Enrichment Evaluation Dalam Pemilihan Perguruan Tinggi Terbaik - Yani, Ahmad; Sumijan, S; Ramadhanu, Agung (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Information technology is a means and object of a system method to organize, transmit, interpret, use, process, obtain, and store data in a meaningful and useful way. Higher education is the form of post-secondary education that includes diploma, bachelor, master, doctoral and vocational programmes, as well as specialized programmes organized by the College based on the culture of the Indonesian nation. The Institute of Higher Education Services (LLDIKTI) is a working unit surrounded by the Ministry of Research Technology, and the Government of higher education that helps to improve the quality of the higher education. Decision support systems combine a variety of techniques and methods aimed at collecting, analysing, and presenting relevant information to support better and more effective decision-making processes. In research using PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) is one of the methods Multi Criteria Decision Making (MCDM) means performing determination or sequencing in a multicriteria analysis. The data used in this study are data of private colleges in LLDIKTI region X of the province of Western Sumatra with a total of 84 Colleges. Private colleges based on calculations using the PROMETHEE method, Private Colleges with the name of Colleges UNIVERSITAS PUTRA INDONESIA YPTK PADANG showed the largest value compared to other Colleges, thus obtaining the best position 1 with leaving flow value 0,58333 entering flow value 0,05556 and net flow value 0.522778. Based on the values obtained, it was concluded that the PROMETHEE method was very effective for use in mating. These results show that the method is capable of producing.